The use of tumour M2-pyruvate kinase as a stool biomarker for detection of colorectal cancer in Hospital Universiti Sains Malaysia - Alhadi, Shahidah Che (2016)
Introduction Stool tests have been used in colorectal cancer screening. Guaiac FOBT is limited by its low sensitivity and specificity. The determination of tumour M2-PK in stool of patients with colorectal cancer and colorectal polyp has been investigated as a potential stool test for colorectal cancer screening. Objectives To evaluate the use of faecal tumour M2-pyruvate kinase test in detection of colorectal cancer and to compare it with the current surveillance tool, guaiac faecal occult blood test.Methodology Symptomatic subjects who were referred for elective colonoscopy in HUSM provided stool samples for analysis of tumour M2-PK and occult blood. For M2-PK test, the stool sample was tested using a commercially available rapid test, ScheBo M2-PK Quick. For gFOBT, the stool sample was sent to HUSM’s laboratory following usual practice to detect faecal hemoglobin. No dietary restrictions were applied for both tests. The results of both tests were compared with colonoscopic result (and/ or with histopathology report).Results 85 subjects (mean age ± SD, 56.8 ± 15.3 years) were enrolled. A total of 17 (20.0%) colorectal cancer and 10 (11.8%) colorectal adenoma were detected. The sensitivity of M2-PK test towards detection of colorectal cancer was higher than gFOBT (100.0% vs 64.7%). However, M2-PK test had a lower specificity when compared with gFOBT (72.5% vs 88.2%). The positive predictive value and negative predictive value of faecal M2-PK test were 47.2% and 100.0% respectively, whereas for guaiac FOBT were 57.9% and 90.9% respectively. Both M2-PK test and gFOBT had low sensitivity towards detection of colorectal adenoma (20.0% vs 30.0%). The specificity of M2-PK test was 54.7%, which was lower than gFOBT which had higher specificity of 78.7%. Conclusion Faecal M2-PK Quick test has a high sensitivity for detection of colorectal cancer as a stool biomarker when compared with gFOBT. It is fast and easy to be performed in clinical settings, thus suitable for initial screening tool for colorectal cancer. Those with positive result should undergo further complete diagnostic evaluation. However, its role for detection of colorectal adenoma is very limited.